2014
DOI: 10.1186/1868-7083-6-19
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic therapy of acute myeloid leukemia using 5-aza-2'-deoxycytidine (decitabine) in combination with inhibitors of histone methylation and deacetylation

Abstract: BackgroundThe silencing of tumor suppressor genes (TSGs) by aberrant DNA methylation occurs frequently in acute myeloid leukemia (AML). This epigenetic alteration can be reversed by 5-aza-2’-deoxcytidine (decitabine, 5-AZA-CdR). Although 5-AZA-CdR can induce complete remissions in patients with AML, most patients relapse. The effectiveness of this therapy may be limited by the inability of 5-AZA-CdR to reactivate all TSGs due to their silencing by other epigenetic mechanisms such as histone methylation or chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 47 publications
3
39
0
Order By: Relevance
“…Caspases play an important role in the regulation and execution of apoptotic cell death [34]. We reported previously that 5-Aza-CdR in combination with DZNep induces a synergistic induction of apoptosis in leukemia cells [35]. We observed that the combination of these epigenetic agents also induce apoptosis in lung carcinoma cells.…”
Section: Discussionsupporting
confidence: 55%
“…Caspases play an important role in the regulation and execution of apoptotic cell death [34]. We reported previously that 5-Aza-CdR in combination with DZNep induces a synergistic induction of apoptosis in leukemia cells [35]. We observed that the combination of these epigenetic agents also induce apoptosis in lung carcinoma cells.…”
Section: Discussionsupporting
confidence: 55%
“…EZH2 and FOXP3 are both involved in the inhibition of autoimmunity and antitumor immunity by Treg cells [129,130], whereas EZH2 itself is involved in the resistance of tumor cells to chemotherapy [111,113] and radiotherapy [131]. Preclinical studies indicate that EZH2 inhibitors are applicable for cancer chemotherapy in combination with other anticancer drugs, such as topoisomerase II inhibitor [111], EGFR inhibitor [132], VEGFR2 inhibitor [133] or HDAC inhibitor [134]. Recently, immune-checkpoint blockers, including anti-CTLA4 antibody, anti-PD1 (PDCD1) antibody and anti-PDL1 (CD274) antibody, are emerging as a new class of cancer therapeutics that augment antitumor immunity [130].…”
Section: Future Perspectivementioning
confidence: 98%
“…ASC senescence and ageing, which is associated with DNA methylation, can be diminished by the application of DNA methyltransferase (DNMT) inhibitors, such as 5‐azacitidine (5‐AZA), which inhibits the methylation pattern of specific gene regions, while activating associated genes. 5‐AZA is chemically an analogue of cytidine, commonly used in the treatment of acute myelogenous leukaemia 24. However, it was shown in human‐aged ASCs that 5‐AZA reversed their aged phenotype, increased proliferative activity and improved osteogenic differentiation potential, while it decreased the accumulation of OS factors and DNA methylation status 25.…”
Section: Introductionmentioning
confidence: 99%